Cumulative irritation, sensitizing potential, phototoxicity and photoallergy of ozenoxacin in healthy adult volunteers. (August 2014) - Gropper, Savion; Cepero, Ana Luisa; Dosik, Jonathan S; LaStella, Phillip; Siemetzki, Heinrich; Wigger-Alberti, Walter
ABSTRACT: : In this series of Phase I, randomized, placebo-controlled studies in healthy volunteers, the potential for ozenoxacin 1 and 2% cream formulations to cause irritation, sensitization, phototoxicity and photoallergy under occlusive patch conditions was evaluated. Both ozenoxacin formulations showed excellent dermal tolerability; in the vast majority of cases, only minimal signs of erythema were observed, with no evidence of edema or a papular response. No subject met the criteria for a phototoxic reaction with the ozenoxacin 1 or 2% cream formulations. Only a few adverse events were reported across repeated-dose studies, and virtually all events were considered to be unrelated or unlikely to be related to ozenoxacin application. Ozenoxacin was safe, well tolerated and showed little or no tendency to cause irritation, sensitization, phototoxicity or photoallergy.